Implementation of different technics for the monitoring of reinforced concretes corrosion applied to rebar embedded in concretes with ordinary and pozzolanic Portland cement - Vazquez, D.R. (2015)
For the development of an intermediate radioactive waste repository, two different types of reinforced concrete were analyzed in terms of durability: one made with ordinary portland cement and the other one made with pozzolanic cement. The values for compressive strength, sorptivity and air permeability demonstrate that the formulations are compatible with the required application. The corrosion rate of rebar up to about 300 days of monitoring and obtained with sensors is below the threshold value required for this type of facilities, except when temperatures are high. The value for the same parameter monitored by the galvanostatic pulse technique using superficial counter electrode and guard electrode is always lower than the threshold value. Additionally, when applying the galvanostatic pulse technique using embedded electrodes, this parameter is comparable to the guard electrode method only when the polarization resistance is calculated through non-linear fitting.